Advanced Electromagnetic Metamaterials for Temperature Sensing Applications - Ma, Liang; Chen, Dexu; Zheng, Wenxian; Li, Jian; Zahra, Sidrish; Liu, Yifeng; Zhou, Yuedan; Huang, Yongjun; Wen, Guangjun (Frontiers in Physics, 2021)
Metamaterials with novel properties have excited much research attention in the past several decades. Many applications have been proposed and developed for the reported metamaterials in various engineering areas. Specifically, for the resonant-type metamaterials with narrow resonance line width and strong resonance strength, the resonant frequency and strength are highly depended on the changings of meta-atom structure and/or substrate media properties induced by the environment physical or chemistry parameters varying. Therefore, physical or chemistry sensing applications for the resonant-type metamaterial units or arrays are developed in recent years. In this mini review, to help the researchers in those fields to catch up with the newly research advances, we would like to summarize the recently reported high-performance metamaterial-inspired sensing applications, especially the temperature sensing applications, based on different kinds of metamaterials. Importantly, by analyzing the advantages and disadvantages of several conventional metamaterial units, the newly proposed high quality-factor metamaterial units are discussed for high-precision sensing applications, in terms of the sensitivity and resolution. This mini review can guide researchers in the area of metamaterial-inspired sensors to find some new design routes for high-precision sensing.